EFEKTIVITAS RITEL MINANG MART BERBASIS KEARIFAN LOKAL SEBAGAI ALTERNATIF FRANCHISE DI KOTA PADANG - ELVIRA MULYA NALIEN (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2020)
Nowadays franchise business is seen as a type of business that promises profits. Especially in minimarket retails such as Indomaret and Alfamart. However, these two mini markets cannot be found in West Sumatra, which actually offers Minang Mart as a modern retail with local wisdom. Minang Mart is the Main Program of TPKAD and is managed by three West Sumatra BUMDs and enlivened by local UMKM. This research is a qualitative research with descriptive approach and inductive method. Data collection using interview techniques, observation and study of related documents. While the Snowball Sampling Technique is used in determining informants. The research purpose is measure the effectiveness of Minang Mart Retail based on local wisdom as an alternative franchise in the Padang city. For this retail effectiveness, it is measured based on effectiveness measurement indicators according to Siagian such as Clarity to Be Achieved, Clarity of Strategies of Goals Achievement, Process of Analysis and Formulation of Strong Policies, Good Planning, Appropriate Programming, Preparation of Supporting Facilities and Infrastructure and Monitoring and Control Systems. Among the indicators that have been going well are Supporting Facilities and Infrastructure.